(untitled) (Agricultural Engineering, 2022)
The analysis of statistical data showed that a large amount of plant waste is generated annually in oil and fat production plants, which must be processed and reused. The paper analyzes the problems of reusing sunflower oil production waste, which is characterized by a relatively high energy value: 1 ton of plant waste is equivalent to 0.625 tons of conventional fuel. According to the mathematical estimation, the actual total amount of impurities is 7.29%, in which major impurities constitute 25.7%. Studies have shown a high probability of oil – containing impurities – 37.25%. Therefore, it is recommended to process such impurities into fuel briquettes and technical oil to increase the profitability of sunflower oil production. For example, at the annual load of technological equipment of the Melitopol Oil Extraction Plant, in 250 days, at a daily processing capacity of 550 t˙day-1, an annual profit of 560,000 EUR is obtainable from the sunflower grain impurities processed into fuel and technical oil.